Stroke Rehabilitation Trends: A Bibliometric Analysis - Patima; Fitri Arofiati (Universitas STRADA Indonesia, 2026)
Backround: Stroke is one of the leading causes of irreversible brain damage and functional disability. Purpose: Explore stroke rehabilitation research trends through bibliometric analysis. Methods: Publication searches from 1997 to 2024 were conducted using the Scopus database. Furthermore, the data obtained was analyzed bibliometrically using VOSviewer version 1.6.20. This analysis includes visualization analysis, co-occurrence analysis, and stroke rehabilitation publication trend analysis. Results: The results of the bibliometric analysis identified 247 publications that met the search criteria in the field of stroke rehabilitation trends. The distribution of publications by country shows that the United States dominates with 83 publications (33.6%), followed by China with 29 publications (11.74%), and Canada with 19 publications (7.69%). This distribution pattern indicates that research on stroke rehabilitation trends remains concentrated in developed countries with high research capacity. These findings confirm that stroke rehabilitation is a topic receiving significant academic attention and continues to evolve globally; therefore, further studies on research trends in this field are considered important to provide direction for the development of more effective stroke rehabilitation interventions in the future. Conclusion: this article provides a comprehensive overview of stroke rehabilitation trends.